The Challenge of Studying Inflation in Precolonial Africa by Klas Rönnbäck – A Response. (27th November 2017) - Green, Toby
Abstract: Following the article by Klas Rönnbäck, this article responds by stressing some key elements missing from the original article. These include the connection of African economic history to world economic history, the question of periodization and economic change, and the issue of currency devaluation in the period in question. The response concludes by posing several questions of the theoretical assumptions made by economists regarding data, and problematizes the applicability of such models to a distant pre-colonial African past. Résumé: À la suite de l'article de Klas Rönnbäck, cet article répond en soulignant certains éléments clés absents de l'article original. Ceux-ci incluent la connexion de l'histoire économique africaine à l'histoire économique mondiale, la question de la périodisation et du changement économique et la question de la dévaluation de la monnaie pendant la période en question. La réponse se termine en posant plusieurs questions sur les hypothèses théoriques des économistes concernant les données, et problématise l'applicabilité de ces modèles à un passé africain précolonial éloigné.